(untitled) (Bangladesh Journal of Botany, 2013)
Genetic diversity analysis among 13 mungbean cultivars from Bangladesh was performed through polymerase chain reaction (PCR) based random amplification of polymorphic DNA (RAPD). Out of 20 arbitrary decamer oligonucleotide primers used, 10 produced a total of 379 different bands with an average of 37.9 bands per primer. Based on the observed banding pattern all the primers were found to be 100% polymorphic. Band size of the amplicons ranged from 250 - 5000 bp. A total of 10 unique DNA fragments was amplified from the 13 mungbean cultivars genome. The values of pair-wise genetic distances ranged from 0.0700 - 1.0852, indicating the presence of wide genetic diversity. The highest genetic distance (1.0852) was found between cultivar BARI Mung-2 and 6 while the lowest (0.0700) between cultivar BINA Mung-2 and 7. Dendogram based on Neis genetic distance using Unweighted Pair Group Method of Arithmetic Means (UPGMA) has segregated the 13 mungbean cultivars into two major clusters. BARI Mung-1, 2, 3, 4 and 5 formed cluster 1 and BARI Mung-6, BINA Mung-1, 2, 7, 6, 4, 5 and 8 have made cluster 2. DOI: http://dx.doi.org/10.3329/bjb.v41i2.13444 Bangladesh J. Bot. 41(2): 169-175, 2012 (December)